Evaluation of ExpressTM 5-PHM and Titanium® 5-PHM Bac®-1 on high-risk receiving steers - Epp, M.P.; Hollis, Larry C.; Barnhardt, B.B.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One backgrounding field study was conducted at two locations to compare the health and performance of high-risk receiving steers given an ExpressTM 5-Pasteurella Haemolytica- Multocida (PHM) vaccine or a Titanium® 5-PHM Bac®-1 vaccine. At one location, calves given the Titanium 5-PHM vaccination had fewer first and second repulls (P<0.05). At the other location, calves given the Express 5-PHM vaccination had fewer initial pulls for respiratory disease and more hospital pen days at initial pull (P<0.05) than those given Titanium 5-PHM. No differences were measured at either location for mortality and average daily gain.
Keywords: Beef; ExpressTM 5-PHM; Titanium® 5-PHM Bac®-1; High risk steers